1993
DOI: 10.1017/s0022029900027631
|View full text |Cite
|
Sign up to set email alerts
|

Influence of switch level of automatic cluster removers on milking performance and udder health

Abstract: SummaryThe effect of a switch level of 200 or 400 g/min for automatic cluster removers on milking performance and udder health was measured with 71 first lactation cows in their first 36 weeks of lactation and with 64 older cows in their first 12 weeks of lactation. Early removal of the milking unit decreased machine-on time by 0·5 min, increased average milk flow rate slightly, improved teat condition significantly and reduced the change in teat end thickness during milking of first lactation cows. Early remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 6 publications
12
61
2
4
Order By: Relevance
“…Studies by Rasmussen (1993) and more recently Stewart et al (2002) demonstrated that by raising the threshold setting of the ACR, milking time could be substantially reduced without affecting yield or the incidence and prevalence of subclinical mastitis. Researchers in Australia reported that assigning a maximum milking time resulted in a 34% reduction in the maximum (5), [246][247][248][249][250][251][252]2010 milking time of the slower-milking cows without signifi cant loss of milk yield (Clarke et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Rasmussen (1993) and more recently Stewart et al (2002) demonstrated that by raising the threshold setting of the ACR, milking time could be substantially reduced without affecting yield or the incidence and prevalence of subclinical mastitis. Researchers in Australia reported that assigning a maximum milking time resulted in a 34% reduction in the maximum (5), [246][247][248][249][250][251][252]2010 milking time of the slower-milking cows without signifi cant loss of milk yield (Clarke et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…If the teat is not refilled with milk quickly enough after the respective quarter is emptied, the compressed teat is re-opening when the liner opens. However, in this case, it opens via the influx of air or milk from outside the teat instead of a refill with milk from the mammary tissue, thus increasing the risk of cross-contamination and infection (Rasmussen 1993).…”
Section: Potential Impact Of Vacuum Fluctuations On Udder Healthmentioning
confidence: 99%
“…Thus, the time of cluster removal is also a matter of discussion. In an experimental study, Rasmussen (1993) showed that automatic cluster removal at a milk flow level of 400 g/min has no negative influence on milking performance and milk yield but shortens milking duration and reduces stress on the teat tissue. Thus, a longer period of milking at very low milk flow rates or even over-milking in certain quarters towards the end of milking can be avoided by a timely cluster removal.…”
Section: Influences Of Teat-end Vacuum On Teat-end Thickness Hyperkementioning
confidence: 99%
See 1 more Smart Citation
“…Taki system powinien mierzyć wypływ mleka z każdej ćwiartki wymienia krowy. Parametry doju będą zmieniać się zależnie od wielkości wypływu mleka [1,8]. Umożliwi to sterowanie procesem doju w obrębie każ-dej ćwiartki i dopasowanie dynamiki doju do cech osobniczych krów.…”
Section: Wprowadzenieunclassified